API CONSUMER SYSTEM APPLIED TO THE PEDAGOGICAL SYSTEMATIZATION OF ARTIFICIAL INTELLIGENCE IN HISTORICAL-CRITICAL PEDAGOGY - Patricio, Thiago Seti; Magnoni, Maria da Graça Mello (Seven Editora, 2026)
The increasing incorporation of Artificial Intelligence (AI) tools in educational contexts has highlighted the need for pedagogical frameworks that guide their use in a critical, intentional, and coherent manner with emancipatory educational projects. In this scenario, Historical-Critical Pedagogy (HCP), grounded in historical-dialectical materialism, presents itself as a theoretical approach capable of offering support for the conscious mediation of technologies in the educational process. However, it is observed that teachers and educational managers face difficulties in systematically articulating the multiple AI tools to the different phases of HCP, especially given the diversity and constant updating of these technologies. This article presents the development and analysis of a system that consumes educational APIs, designed to organize, record, and relate pedagogical uses of AI to the phases of HCP: initial social practice, problematization, instrumentalization, catharsis, and final social practice. The system acts as a data-consuming layer for data from an external Application Programming Interface (API) of AI tools, based on the PedagogIA guide, both developed by the author. This allows the teacher to select a tool, associate it with one or more phases of the PHC (Pedagogical History) process, and describe, for each link, a pedagogical explanation and a practical example of its application in teaching contexts. From a methodological point of view, the work is characterized as applied research, with a qualitative and exploratory approach, supported by the development of educational software. The system architecture was structured according to the client-server model, in which the consumer is responsible for the pedagogical mediation of the technical data provided by the API, promoting the didactic re-signification of technological information. The interface was developed to favor teacher reflection, stimulating theoretically grounded pedagogical planning. The results indicate that the system contributes to the organization of pedagogical thinking about the use of AI, by shifting the focus from the tool itself to its educational function at each moment of the formative process. Furthermore, the proposal highlights the potential of API-based architectures to support the construction of critical educational environments, in which technology is not an end, but a means subordinated to a conscious pedagogical project. It concludes that the integration between API-consuming systems and Historical-Critical Pedagogy (HCP) can favor more reflective, systematized pedagogical practices aligned with integral human development. DOI: https://doi.org/10.56238/sevened2026.001-034